2021
DOI: 10.1080/11287462.2021.1896453
|View full text |Cite
|
Sign up to set email alerts
|

Researchers’ perspectives on return of individual genetics results to research participants: a qualitative study

Abstract: Genetic results are usually not returned to research participants in Uganda despite their increased demand. We report on researchers' perceptions and experiences of return of individual genetic research results. The study involved 15 in-depth interviews of investigators involved in genetics and/or genomic research. A thematic approach was used to interpret the results. The four themes that emerged from the data were the need for return of individual results including incidental findings, community engagement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“… 1 2 Research to determine preferences and perspectives of African stakeholders on the feedback of individual genetic results to participants in genomics research projects (feedback of findings; FoFs) is ongoing. 3 4 This supports the call to action for understanding contextual factors in African communities that impact on decision-making regarding FoFs and guides development of national and regional guidelines. Globally, the subject of return of genetic results including incidental findings has gained momentum in favour of disclosure of clinically actionable genomic findings from research studies in an ethically and legally appropriate manner.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“… 1 2 Research to determine preferences and perspectives of African stakeholders on the feedback of individual genetic results to participants in genomics research projects (feedback of findings; FoFs) is ongoing. 3 4 This supports the call to action for understanding contextual factors in African communities that impact on decision-making regarding FoFs and guides development of national and regional guidelines. Globally, the subject of return of genetic results including incidental findings has gained momentum in favour of disclosure of clinically actionable genomic findings from research studies in an ethically and legally appropriate manner.…”
Section: Introductionmentioning
confidence: 54%
“…Consider other factors which may determine strategies for FoFs, including stakeholder views and experiences on implementation of FoFs, context, age of participants, socioeconomic situation, disease conditions, demographics, funding resources and perceived outcomes of FoFs. Recent work by Mswaka et al 3 reported on community perceptions and individual preferences for the return of results in Uganda and a need to build national guidance to support genetic research. More localised research is critical to determine the best ways to implement FoFs in African settings.…”
Section: Conclusion and Further Recommendationsmentioning
confidence: 99%
“…This might be due to the non-physical nature of risks involved in genomic and genetics research and the uncertainty of the future studies at the time of consenting. Generally, the poor understanding of genetics-related information is not limited to research participants only, studies have shown that various stakeholders, including investigators have limited understanding of genetic and genomic concepts (Kengne-Ouafo et al, 2016; Mwaka et al, 2021; Ogunrin et al, 2019; Tindana et al, 2012). Therefore, we would not expect a research participant to adequately understand informed consent when the investigator obtaining it does not sufficiently understand genetics and genomic research and its implications.…”
Section: Discussionmentioning
confidence: 99%
“…To date, this is the first South African study conducted to map the experiences of health professionals regarding the practice of WES and return of IFs. Mwaka et al (2021) conducted a qualitative study on Ugandan researchers’ perspectives on return of individual genetic findings to research participants. They asserted that community engagement, reconsenting and adequate preparation of participants to safely receive individual results, may be achieved by building capacity and increasing access to clinical genetics and genetic counselling (GC).…”
Section: Introductionmentioning
confidence: 99%